Adapting the personality‐targeted Preventure program to prevent substance use and associated harms among high‐risk Australian adolescents. Issue 4 (26th November 2013) - Barrett, Emma L.; Newton, Nicola C.; Teesson, Maree; Slade, Tim; Conrod, Patricia J.
Abstract Aim Substance use among adolescents is of significant concern and the need for preventive interventions is clear. Although universal prevention programs have shown to reduce substance use among Australian adolescents, no effective selective program has been developed for high‐risk youth in Australia. Preventure is a personality‐targeted intervention that has shown to be effective in the UK and Canada and is yet to be trialled in Australia. Before doing so, it is necessary to ensure the content is relevant for the Australian setting. This study reports data collected to update and adapt the UK‐based Preventure program for use in Australia. Methods Eight focus groups were conducted with 69 students from three secondary schools in Sydney, Australia. Students who screened high risk for early‐onset substance misuse were invited to participate in focus groups specific to their personality profile and provide feedback. Written feedback was also obtained from 12 teachers and health professionals. Results Students, teachers and experts recommended specific changes to the content, language, scenarios and graphics of the Preventure manuals. The majority of teachers and experts believed that the educational content of the program was appropriate for students and that it would be effective in reducing substance use in this population. Conclusions The information obtained in the current study was used to update the Preventure program for use with Australian adolescents. It is expected that this modified Preventure program will demonstrate similar effects in reducing alcohol and drug use among high‐risk youth in Australia, as it did in the UK and Canada.